金属带式无级变速传动（CVT）装置关键件结构强度分析 - 孙冬野; 秦大同; 杨亚联 (Jixie chuandong)
In this paper, the distribution of structural strength of key components in a metal V belt continuously variable transmission （CVT） is analyzed by finite element method. The change relation between compression forces in steel rings and/or metas blocks and speed ratio is discussed. And some measures are also put forward to solve the problems in designing a metal V belt CVT.